The Role of Vitamin D in COVID-19 and the Impact of Pandemic Restrictions on Vitamin D Blood Content - Tomaszewska, Agata; Rustecka, Agnieszka; Lipińska-Opałka, Agnieszka; Piprek, Rafal P.; Kloc, Małgorzata; Kalicki, Bolesław; Kubiak, Jacek Z. (Frontiers in Pharmacology, 2022)
Vitamin D is a hormone regulating the immune system and playing a pivotal role in responses to microbial infections. It regulates inflammatory processes by influencing the transcription of immune-response genes in macrophages, T cells, and dendritic cells. The proven role of vitamin D in many infectious diseases of the respiratory tract indicated that vitamin D should also play a role in SARS-CoV-2 infection. Vitamin D inhibits cytokine storm by switching the pro-inflammatory Th1 and Th17 to the anti-inflammatory Th2 and Treg response. Vitamin D is therefore expected to play a role in preventing, relieving symptoms, or treating SARS-CoV-2 infection symptoms, including severe pneumonia. There are several possible mechanisms by which vitamin D may reduce the risk of COVID-19 infection, such as induction of the transcription of cathelicidin and defensin. Currently, there is still insufficient scientific evidence to support the claim that vitamin D supplementation may help treat COVID-19 infection. The pandemic restrictions were also shown to impact vitamin D uptake by limiting exposure to sunlight.